Obtaining and scintillation properties of crystals based on Eu²⁺ doped Ba(Br₀.₉Cl₀.₁)₂ solid solution - Cherginets, V.L.; Datsko, Yu.N.; Grippa, A.Yu.; Ponomarenko, T.V.; Rebrova, N.V.; Rebrova, T.P.; Gorbacheva, T.E.; Lopin, A.V.; Trubaeva, O.G.; Pedash, V.Yu. (Functional Materials, 2015)
Scintillation crystals based on BaBr₂-BaCl₂ solid solution corresponding to minimal melting point in the phase diagram doped with Eu²⁺ (from 0.3 to 3 mol. %) were grown by Bridgman-Stockbarger method. The X-ray luminescence spectra of pure matrix of Ba(Br₀.₉Cl₀.₁)₂ composition includes wide emission band with the maximum which position is placed near 410 nm. The emission spectra of the Eu²⁺-activated materials contain narrow bands with the maxima at 411-413 nm. The absolute light yield of Ba(Br₀.₉Cl₀.₁)₂:Eu²⁺ material doped with 3 mol. % of the activator is ca. 32600 photons per MeV and the best energetic resolution is 9.5 %. The decay curve for the studied materials is described by one component with the time constant of 70 ns. Distribution coefficient of Eu²⁺ in the studied matrix is estimated as k = 0.72±0.05. All the obtained parameters are close to those of BaBr₂:Eu²⁺ single crystals obtained under similar conditions.